Radiological contribution to the diagnosis of early postoperative complications after lung resection for primary tumor: a revisional study - Cardinale, Luciano; Priola, Adriano Massimiliano; Priola, Sandro Massimo; Boccuzzi, Francesco; Dervishi, Najada; Lisi, Elena; Veltri, Andrea; Ardissone, Francesco (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
In the post-operative course of the interventions of lung resection for primary tumor, complications of different nature and severity can arise, recognizing different pathogenetic mechanisms and differing according to the type of resection performed and to the time elapsed after surgery. The low diagnostic accuracy of chest radiography requires a thorough knowledge of the radiologist about all radiographic findings, both normal and pathological, which can be found in the immediate post-operative period (within 30 days after surgery). This article aims to describe the incidence, the clinical features and the radiological aspects of immediate complications following pulmonary resections, with specific reference to those in which the diagnostic imaging provides a fundamental contribution.